Efficacy and Safety of Ferric Carboxymaltose for Iron-Deficiency Anemia (IDA) in Postpartum Women: An Observational Study (Medical Forum Monthly, 2024)
Objective: To assess the efficacy and safety of ferric caboxymaltose in postpartum women with iron deficiency anemia using single dose infusion in a tertiary care hospital.Study Design: A single center, single-arm observational studyPlace and Duration of Study: This study was conducted at the Ziauddin Hospital Keamari, Karachi which is affiliated with Ziauddin University, Karachi from April, 2014 and November, 2014.Materials and Methods: A single center, single-arm observational study was conducted at Ziauddin Hospital Keamari, Karachi which is affiliated with Ziauddin University between April, 2017 and November, 2017. A total of 60 women 10 days or less after delivery with postpartum Hb less than 9g/dl diagnosed as iron deficiency anemia. The dosage of ferric carboxymaltose was fixed as 1000mg diluted in 100 ml normal saline infused in 30 minutes or less, for all the patients. CBC, serum iron, serum ferritin, TIBC were performed prior to administration of ferric carboxymaltose and then repeated after week 2 and week 4. The primary efficacy end point was the change in Hb from baseline to week 4.Secondary efficacy endpoints included change in Hb and other serum iron parameters. A secondary outcome measure was occurrence of adverse events from baseline to week 4.Results: There was a statistically significant improvement in haemoglobin levels over a period of 4 week (day 0 - 14 p<0.001, day 0 - 28 p<0.001). The mean MCV was not found to be statistically significant between baseline and week 2 and week 4 (p = 0.158, p = 0.658).We found a statistically significant improvement in TSAT and serum ferritin from baseline to week 2 and week 4 (p <0.001).Conclusion: In conclusion, ferric carboxymaltose seems to be the drug of choice if I/V iron treatment during postpartum period becomes necessary. Our study shows that the tolerance of ferriccarboxymaltose in pregnancy is excellent, and prevalence of side effects is low, in the postpartum period.